Factors that influence parenting styles at Early Childhood Education level in Magwegwe Cluster of Mzilikazi District in Bulawayo Metropolitan Province. - Senda, Diana Roselyn (Midlands State University, 2019)
The study was carried out to find factors that influence the use of different parenting styles in Early Childhood Education level in Magwegwe cluster of Mzilikazi District in Bulawayo Province. The background of the study highlights varying parenting styles within communities despite having great impact on behavior of children and development. This prompted the researcher to find out factors that influence use of different parenting styles with the hope of finding ways of maintaining positive influences. Below are the sections covered: i. Topic– Factors that influence parenting styles at early childhood education level in Magwegwe cluster. ii. Methodology- The study used the descriptive survey as it is a social phenomenon, it sought to find out relationships between social activities and child rearing. iii. Findings -The study found out that use of parenting styles have influential factors such as, socioeconomic status, maternal employment, cultural background and family type. iv. Conclusions- From the study findings it is confirmed that the choice of parenting style used is influenced by some factors among families, for instance the culture of family, socioeconomic status, employment, type of family among others. v. Recommendations- Researcher recommends that parents be enlightened on effects of different parenting styles to development so that they choose them from an informed decision.  Single parents to engage extended family in child rearing as they can be supportive in such cases.  Taking culture in cognisance in imparting good morals and values of the family hence achieving proper social development.  Parents, guardians and teachers to be good role models for children to imitate.